Differentiating Role of Agro-Climatic Conditions in the Development of Grain Farming in the Region - TARSHILOVA, Lyudmila S.; IBYZHANOVA, Aizhan J.; YERZHANOVA, Zhanar K.; SULTANOV, Akylbek U.; AMANGALIEVA, Zinat K. (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The article presents estimation of agro-climatic conditions in terms of their influence on spatial location of grain farming in West Kazakhstan Region as well as dependence of grain crop yield on moisture conditions, which is determined based on correlation-regression analysis. Moreover, the article presents the forecast of grain crop yield. A clearly expressed zonal distribution of the agricultural sector of a region affects the spatial location of grain farming. The regional grain farming is characterized by extreme instability and variability in development that can be leveled through the use of modern agronomic technologies.
Keywords: grain farming; agro-climatic conditions; natural resource potential; yield; forecasting